Springtime Peaks and Christmas Troughs: A National Longitudinal Population-Based Study into Suicide Incidence Time Trends in the Netherlands - Hofstra, Emma; Elfeddali, Iman; Bakker, Marjan; de Jong, Jacobus J.; van Nieuwenhuizen, Chijs; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2018)
Background: Time trends are one of the most studied phenomena in suicide research, however, evidence for time trends in the Dutch population remains understudied. Insight into time trends can contribute to the development of effective suicide prevention strategies. Methods: Time trends in national daily and monthly data of 33,224 suicide events that occurred in the Netherlands from 1995 to 2015 were examined, as well as the influence of age, gender and province, in a longitudinal population-based design with Poisson Regression Analyses and Bayesian Change Point Analyses. Results: Suicide incidence among Dutch residents increased from 2007 until 2015 by 38%. Suicide rates peak in spring, up to 8% higher than in summer (p<.001). Suicide incidence was 42% lower at Christmas, compared to the December-average (IRR=0.580, p<.001). After Christmas, a substantial increase occurred on January 1, which remained high during the first weeks of the new year. Suicide occurred more than twice as often in men than in women. For both genders the results indicated a spring time peak in suicide incidence and a trough at Christmas. Suicide rates were highest in the elderly (age group 80+) and no evidence was found of a differential effect by season in the age groups with regard to suicide incidence.. No interaction effect was found with regard to province of residence for both season and Christmas, indicating that no evidence was found that these time trends had differential effects in the Dutch provinces in terms of suicide incidence. Conclusion: Evidence was found for time trends in suicide incidence in the Netherlands. It is recommended to plan (mental) health care services to be available especially at high risk moments; at spring time and in the beginning of January. Further research is needed to explore the protective effect of Christmas in suicide incidence.